2018 Joint Thermophysics and Heat Transfer Conference, Atlanta, Georgia, USA, 25-29 June 2018. (American Institute of Aeronautics and Astronautics, 2018)
The conference is designed by the technical experts of AIAA - American Institute Of Aeronautics And Astronautics, Inc. The program is dedicated to provide a huge form for leading researchers and scientists to discuss on all aspects of thermal science and engineering related to aerospace applications. The program will also focus on basic research and development to applied and advanced technology, including novel experimental and computational observations.